Nutrient Storage and Utilisation under Forest Ecosystems in Cold Deserts of Himachal Pradesh, India - Poonam; Bawa, R. (Indian Forester, 2020)
The present study was conducted in Goshal, one of the largest villages of cold desert district Lahaul in Himachal Pradesh, India, during 2010 to 2013 to study the nutrient status and their utilisation in forest ecosystem for understanding the importance, utilization and exploitation offorest area and intricate utilization ofnutrients in cold deserts oflndia. For estimation ofdifferent plant nutrient contents from the different area of forest the whole ecosystem was divided into nine grids forsampling. We found that the leafnitrogen content in tree species were found maximum in Juniperus macropoda (2.28%) and least in Salix fragilis (1.33%). Similarly among the shrubs the leafnitrogen, phosphorus, potassium and calcium contents were found maximum in Ephedra gerardiana, while nitrogen was maximum 2.06% in in Ephedra gerardiana. The present study generates a strong database, for estimating the present nutrient status of various natural resources and it would be of great help for researchers working in such harsh areas in other parts of the world, planners and decision makers for drawing interlinked sustainable developmental plans.